Psychological particular qualitiesof partnership interaction between teachers and parents of a child with special educational needs in the context of inclusive education (Actual Problems of Psychology in Educational Institutions, 2021)
The article examines the problem of normalizing the interactionbetween a teacher and parents of children with special educational needs onthe basis of partnership pedagogy. Attention is focused on the specificity ofthe psychological state of a family raising a child with special educationalneeds as a prerequisite for complicating the cooperation of all members ofthe team of psychological and pedagogical support. An attempt is madeto highlight the psychological aspects for harmonizing the partnershipbetween parents and teachers in an inclusive educational environment.
Keywords: partnership pedagogy; teacher-parent cooperation; a child with special educational needs; inclusive education; , a team of psychological and pedagogical support